In Vitro Investigation of Therapeutic and Anti-Coagulant Properties of Allium Sativum L. on Human Plasma - Sarfraz, Sadaf; Khan, Muhammad Ismail; Sikandar, Shomaila; Ismail, Anam (BioScientific Review, 2022)
The current study was conducted to compare the anti-coagulant activity of different solvent-extracted fractions of garlic in a human blood sample in vitro. Two different solvents, namely rectified spirit and reverse osmosis (RO) water, were used to achieve the desired results. We used multiple extracting approaches to prepare different extract fractions of Allium sativum, both in ethanolic and aqueous extracts. These approaches included maceration, decoction, and soxhlet extraction methods. The concentration of each extract fraction was subjected to a primarily anti-coagulant screening method applied to a human blood sample in vitro by calculating the prothrombin time of human blood coagulation. The anti-coagulant activity of the extracts was determined by measuring the changes in prothrombin time with a null hypothesis value of p< 0.05. Additionally, a qualitative study of active phytochemical elements, such as alkaloids, flavonoids, steroids, proteins, carbohydrates, terpenoids, tannins, and glycosides was also conducted. The results indicated that all garlic extract fractions have a significant anti-coagulant potential. However, at 5 ppm concentration, soxhlet extraction extract showed the maximum anti-coagulant potential. Moreover, Garlic’s aqueous extract also showed a significant anti-coagulant effect on human plasma. This observation conforms to the finding that the soxhlet extracted sample of garlic showed the highest activity of platelet aggregation inhibition. Furthermore, it was determined that aqueous and ethanolic extracts of Allium sativum showed a significant potential of anti-coagulation by comparing the current results with positively controlled EDTA and double oxalate acting as synthetic anti-coagulants.